Do Parents Buy Their Children's Attention? - Annika Meng (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
Past empirical studies on the strategic bequest motive have found evidence for the existence of a positive causation of wealth on receiving attention from on's children. This paper illustrates that these results from the past should be interpreted with some care as the relationship between wealth and children's attention is sensitive to the type of financial variable used in the analysis. Only family characteristics are significant determinants of contact behavior. Turning to more serious types of physical needs, care behavioral regressions illustrate that mobility constraints like house ownership for parents or job and location restrictions for children hamper informal care provision by one's children.
Keywords: D12; D31; J14; 330; Strategic bequest; imputation; elderly care; Altenhilfe; Kinder; Familiensoziologie; Erbe; Motivation; EU-Staaten